Simulação ab initio de nanotubos de carbono funcionalizados via adsorção e deformação estrutural - Lara, Ivi Valentini (2014)
In this thesis the behavior of functionalized carbon nanotubes via chemical and physical adsorption and estrural deformation is studied through ab initio calculations based on the DFT formalism, using the SIESTA program. First, we evaluated the behavior of CNTs functionalized with COOH group and it was observed that their position on different sublattices modifies the Carbon nanotube electronic properties, besides the fact that the electronic nature of a semiconductor CNT can be modulated from the concentration of carboxylation. The behavior of armchair CNTs radially deformed was evaluated and it was observed that by the limit of the radial deformation, the electronic character of the nanotubes were keeped as metallic, although the interaction between the walls increases as the deformation increases. The elastic constant values of deformed CNTs with more than one wall indicates the contribution of each individual nanotube constituting the system in its structural and elastic properties. The vibrational frequencies calculated reflect the effect of deformation of the CNTs, as the deformation increases, its frequency decreases. We evaluated the synergistic effect of chemical functionalization of CNTs deformed with the COOH group. For the external functionalization process, more curved region promotes the carboxylation process, whilst for the internal, the COOH group remains confined and does not bind covalently to its wall. Finally, we evaluated the physical adsorption of lithium in deformed CNTs with two layers. Both between the layers, like its exterior, lithium donates charge to the nanotube, not changing its electronic character. The adsorption process of lithium between the walls of deformed CNT is more efficient than on its exterior, in particular for radially deformed configurations.